2013
DOI: 10.1111/age.12066
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional analysis of intramuscular fatty acid composition in the longissimus thoracis muscle of Iberian × Landrace back‐crossed pigs

Abstract: This study aimed at identifying differential gene expression conditional on the fatty acid profile of the longissimus thoracis (Lt) muscle, a prime cut of economic relevance for fresh and cured pork production. A population of 110 Iberian (25%) × Landrace (75%) back-crossed pigs was used, because these two breeds exhibit extreme profiles of intramuscular saturated fatty acid, monounsaturated fatty acid (MUFA) and polyunsaturated fatty acid (PUFA) contents. Total RNA from Lt muscle was individually hybridized t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 63 publications
(69 reference statements)
4
19
0
Order By: Relevance
“…Also, ECM components (mainly collagen genes) and functions have been detected as differential in comparison studies among populations differing in intramuscular fat composition, due to breed or dietary factors [15, 17, 51, 52]. These previous results together with the present ones reinforce the ECM biological importance in determining composition and organization of muscle tissue, as well as its significance in the regulation of IMF deposition.…”
Section: Resultssupporting
confidence: 77%
“…Also, ECM components (mainly collagen genes) and functions have been detected as differential in comparison studies among populations differing in intramuscular fat composition, due to breed or dietary factors [15, 17, 51, 52]. These previous results together with the present ones reinforce the ECM biological importance in determining composition and organization of muscle tissue, as well as its significance in the regulation of IMF deposition.…”
Section: Resultssupporting
confidence: 77%
“…In previous studies of our group, we observed that in liver [4], a high content of PUFA (H group phenotype) shifted the metabolism towards the FA oxidation; meanwhile, in adipose tissue [5] inhibited lipogenesis. Accordingly, in other studies analyzing the muscle transcriptome using microarrays a favored FA oxidation and a reduced fatty acid uptake, lipogenesis and triacylglycerol synthesis was generally observed in the group with higher intramuscular PUFA content [27], [35]. In our RNA-Seq study in muscle we observed an inhibition of glucose uptake and lipogenesis in the H group, which would produce a decrease in the triglyceride storage.…”
Section: Discussionsupporting
confidence: 55%
“…Moreover, two of the differentially-expressed genes in muscle ( AQP7 and FOS ) were also identified as differentially expressed in liver [4], and seventeen of them ( AQP4, SCD, PLEKHB1, CTSF, CIDEC, ALDOC, CXCL2, KIAA0408, SLPI, ALB, C14H10orf116, ITPR2, TRIP10, BANF1, HIF1AN, CHAC1 and FHL3 ) were identified as differentially expressed in adipose tissue [5]. In addition, three of the differentially-expressed genes in our analysis ( ATF3, ENAH and SLPI ) were also identified in a muscle microarray study of extreme animals for FA composition from the same backcross [27]. Other genes such as DNAJA4, ANKRD1, MYH10 and TNFRSF12A were also common, but they were only detected by the DESeq program [25] in the RNA-Seq data.…”
Section: Resultsmentioning
confidence: 92%
“…The glycolytic pathway is important in the first steps of glucose conversion into lipids, and de novo lipogenesis is directly involved in IMF deposition in pig muscles (Mourot & Kouba 1999). This seems to be the case in pig muscle, as fatter animals have higher mRNA levels for both lipogenic and lipolytic enzymes Canovas et al 2010;Pena et al 2013). This seems to be the case in pig muscle, as fatter animals have higher mRNA levels for both lipogenic and lipolytic enzymes Canovas et al 2010;Pena et al 2013).…”
Section: Gene Expression Differences Between Pigs Of Distinct Geneticmentioning
confidence: 99%
“…Comparison of transcriptomic levels between pigs from the same population but with divergent muscle phenotypes also has been used to study IMF deposition in the longissimus dorsi Hamill et al 2012) and muscle lipid content and composition in the gluteus medius (Canovas et al 2010) and longissimus dorsi (Pena et al 2013). These three reports highlighted the prominent role of glycolytic enzymes on IMF deposition and revealed a general trend towards promoting lipogenesis at the expense of lipolysis in fatter pigs.…”
Section: Gene Expression Differences Between Pigs Of Distinct Geneticmentioning
confidence: 99%